Proceedings of the Tenth International Conference on Learning Analytics &Amp; Knowledge 2020
DOI: 10.1145/3375462.3375527
|View full text |Cite
|
Sign up to set email alerts
|

Understanding students' engagement with personalised feedback messages

Abstract: Feedback is a major factor of student success within higher education learning. However, recent changes -such as increased class sizes and socio-economic diversity of the student population -challenged the provision of effective student feedback. Although the use of educational technology for personalised feedback to diverse students has gained traction, the feedback gap still exists: educators wonder which students respond to feedback and which do not. In this study, a set of trackable Call to Action (CTA) li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Especially when it c omes to flipped classrooms, provision of clear guidelines and feedback on students' learning strategies is important so that they understand how to prepare for tutorials (Akçayır & Akçayır, 2018). However, providing effective feedback has become more difficult in recent years (Iraj et al, 2020;Lim et al, 2021;Pardo et al, 2019). Changes in higher education have led to educators seeking novel ways to provide timely, personalised feedback to students to promote their SRL (Pardo et al, 2019).…”
Section: Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially when it c omes to flipped classrooms, provision of clear guidelines and feedback on students' learning strategies is important so that they understand how to prepare for tutorials (Akçayır & Akçayır, 2018). However, providing effective feedback has become more difficult in recent years (Iraj et al, 2020;Lim et al, 2021;Pardo et al, 2019). Changes in higher education have led to educators seeking novel ways to provide timely, personalised feedback to students to promote their SRL (Pardo et al, 2019).…”
Section: Feedbackmentioning
confidence: 99%
“…Despite this limitation, the findings identify technology -mediated feedback as a promising tool for supporting SRL. Previous research demonstrates LA based feedback is effective in improving students' engagement, satisfaction, and performance (Banihashem et al, 2022, Iraj et al, 2020Lewis et al, 2021;Pardo et al, 2019). LA based feedback may aid students by way of internal and external task factors (Winne & Hadwin, 1998), whereby students receive automated, yet personalised, feedback on their engagement or performance, to inform SRL strategy monitoring (i.e., via the evaluations process).…”
Section: Utilising Technology-mediated Feedback To Support Students' ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The Pearson correlation coefficient is used to measure the relationship between the dependent and independent variables. The regression analysis is employed to determine the effectiveness of the model in predicting students' outcomes [14] Course success and feedback engagement…”
Section: Sourcementioning
confidence: 99%
“…Taking action requires a student capability termed proactive recipience of feedback . A lack of research examining how students interact with and are transformed by computer-assisted or produced feedback (Iraj, Fudge, Faulkner, Pardo, & Kovanović, 2020) limits the ability to build student capability and improve learning outcomes. Research on student feedback across institutions has shown that feedback that works for students encourages their active learning and, according to Molloy, Boud, and Henderson (2020), "called to action in some way" (p. 534).…”
Section: Introductionmentioning
confidence: 99%